Permeabilization of ultraviolet-irradiated Chinese hamster cells with polyethylene glycol and introduction of ultraviolet endonuclease from Micrococcus luteus. - Yarosh, D B (1981)
Chinese hamster V-79 cells were made permeable by treatment with polyethylene glycol and then incubated with a Micrococcus luteus extract containing ultraviolet-specific endonuclease activity. This treatment introduced nicks in irradiated, but not in unirradiated, deoxyribonucleic acid. The nicks remained open for at least 3 h; there was no loss of endonuclease-sensitive sites, and no excision of dimers as measured by chromatography was detected. In addition, there was no increase in ultraviolet resistance in treated cells. This suggests that the absence of a significant amount of excision repair in rodent cells is due to the lack of both incision and excision capacity.